Financial Frictions in Data : Evidence and Impact - Taheri Sanjani, Marzie (IMF Working Papers; Working Paper ;, 2014)
This paper investigates financial frictions in US postwar data to understand the interaction between the real business cycle and the credit market. A Bayesian estimation technique is used to estimate a large Vector Autoregression and New Keynesian models demonstrating how financial shocks can have a large and sluggish impact on the economy. I identify the default risk and the maturity mismatch channels of monetary policy transmission; I further employ a generalized-IRF to establish countercyclicality of risk spreads; and I show that the maturity mismatch shocks produce a stronger impact than the default risk shocks.